A comparative study on the applicability of ultracapacitor models for electric vehicles under different temperatures. (15th June 2017) - Wang, Chun; He, Hongwen; Zhang, Yongzhi; Mu, Hao
Highlights: A systematic experimental procedure is established in details. A GA based parameter identification method was evaluated. Five typical UC models have been compared under different temperatures and SOCs. The effectiveness of the modeling method has been evaluated in UC pack modeling. Abstract: This paper presents a systematic evaluation for five typical equivalent circuit models (ECMs) of ultracapacitors (UCs) under different ambient temperatures. A comprehensive experimental profile is designed to obtain the test datasets. The genetic algorithm (GA) is employed to identify the model parameters for five UC models under different temperatures and state of charge (SOCs). Three results can be obtained from the systematic analysis. (1) Due to the better model accuracy and robustness, the Thevenin model is preferred for UC cell modeling with the maximum errors less than 8 mV. (2) Compared with the other four UC models, the Thevenin model with one-state hysteresis (Thevenin-hys model) is preferred for UC pack modeling because of its better performance. (3) From the point of view of model accuracy and robustness against different ambient temperatures, if the SOC is less than 0.5, the UCs are not suitable for further application.